(untitled) (Research, Society and Development, 2022)
Objective: To describe the protocol and methodology used to carry out a scope review that will map the scientific evidence on the theoretical frameworks used in nursing care in the field of mental health. Methodology: Scope review developed according to the recommendations of the Joanna Briggs Institute. In writing the study, the PRISMA Extension for Scoping Reviews will be used. A comprehensive search will be carried out in the MEDLINE/PubMed, Web of Science Core Collection/ Clarivate Analytics, Scopus, Cochrane Library, CINAHL, Biomedical Answers (EMBASE), LILACS/BVS databases and databases, in addition to the gray literature search in Google bases Scholar, ProQuest and OpenGrey. Primary and secondary studies that address nursing theories in the context of mental health will be included, and letters, comments, editorials and opinion articles will be excluded. Selection of studies by reading the titles, abstracts and full text conducted by two independent reviewers. Data extraction performed through a form built based on JBI recommendations. The data will be organized, summarized and analyzed for extent, nature, distribution and recurrent patterns, and the results will be communicated narratively through network maps. Final considerations: It is expected that this study will contribute to the strengthening of the use of nursing theories in mental health care, in addition to helping nurses in practice, research, education and administration in the dimensions of care.